“HIV/AIDS Isn’t Here”: A Case Study of a One-Week Recreational Camp for Individuals Affected by HIV - Hyba, Naomi (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2016)
In this case study we examine the experiences of campers and volunteers at a one-week residential camp for individuals and families affected by HIV in Canada. The data presented was gathered during the camp session held in July 2013, and was derived from 26 interviews with campers and volunteers and from 40 self-administered surveys. This data highlights five themes: the camp as a “family” with a strong sense of community; a sense of belonging not experienced elsewhere due to stigma; the crucial role of peer social support; the camp as the intersection of diverse cultural and social groups; and reduced significance of one’s HIV status in the camp environment. This study recommends that social workers, whose caseloads include HIV-affected individuals or families, make greater use of such camps -- for example, systematic referrals, to boost social support. This article also calls on social workers to invest themselves in this type of community programming in order to enhance the quality and quantity of services offered.